2004
DOI: 10.1002/acp.1028
|View full text |Cite
|
Sign up to set email alerts
|

The influence of an early interview on long‐term recall: a comparative analysis

Abstract: Because of burgeoning participation by children in forensic situations there is significant concern about children's memory for stressful events. Influence of timing of the first interview and interview frequency on long‐term recall were evaluated by comparing three groups of 3‐ to 9‐year‐olds 1 year after an injury requiring emergency room treatment. One group had one interview, a year after injury; another group had two interviews, immediately and a year later; the third group had three interviews, immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 54 publications
5
24
1
Order By: Relevance
“…A possible explanation is that the early and highly detailed interview reinstated the event so effectively that differences between stress groups in completeness and accuracy were counteracted in later interviews. In fact, the efficacy of an earlier interview in reinstating parallel complex events has been demonstrated in earlier work with preschoolers (Peterson, Pardy, TizzardDrover, & Warren, 2005;Tizzard-Drover & Peterson, 2004). This lack of long-term stress effects replicates findings of some other research.…”
Section: Discussionsupporting
confidence: 71%
“…A possible explanation is that the early and highly detailed interview reinstated the event so effectively that differences between stress groups in completeness and accuracy were counteracted in later interviews. In fact, the efficacy of an earlier interview in reinstating parallel complex events has been demonstrated in earlier work with preschoolers (Peterson, Pardy, TizzardDrover, & Warren, 2005;Tizzard-Drover & Peterson, 2004). This lack of long-term stress effects replicates findings of some other research.…”
Section: Discussionsupporting
confidence: 71%
“…Those with early interviews (within the first week) had more accurate recall after 1 year, suggesting that an early opportunity to talk about the event through an organized and systematic interview helped their recall a year later. This beneficial effect of an immediate interview was also found by Tizzard-Drover and Peterson (2004): 3-to 4-year-olds (although not older children) had greater recall and accuracy about their injury and hospital treatment that had occurred a year earlier if they had an interview shortly after the event. However, these beneficial effects were no longer discernible after a delay of 2 years in interviews about the pirate event (Pipe et al, 2004) or injury (Peterson et al, 2005).…”
mentioning
confidence: 53%
“…Likewise, Pipe, Sutherland, Webster, Jones, and La Rooy (2004) found that interim interviews helped 5-to 7-year-olds recall a pirate event at both 1 and 2 years. More pertinent to the present study is the research by Peterson and her colleagues: Tizzard-Drover and Peterson (2004) interviewed 3-to 9-year-olds about injuries resulting in emergency room treatment after 1 year, with some children having had prior reinstating interviews and others not, and these children were followed up after 2 years by Peterson, Pardy, Tizzard-Drover, and Warren (2005). For 3-to 4-year-olds, having an early reinstating interview fostered better recall at 1 year, and after 2 years, recall for the hospital event (although not their injury) was still poorer if they had not had early reminders of the event through early interviews.…”
mentioning
confidence: 99%
“…In terms of children's recall of injuries requiring emergency room treatment, the effect of multiple interviews on completeness of injury prototype components and their proportion accuracy were explored in two previous studies of 3-to 9-year-olds. The first compared (a) children who had three interviews, immediately after injury and again 6 months and 1 year later, (b) children who had two interviews, immediately after injury and 1 year later, and (c) children who had only one interview, 1 year after injury (Tizzard-Drover & Peterson, 2004). Having an immediate interview (regardless of whether there was an extra one at 6 months) resulted in 3-and 4-year-olds having more complete and more accurate recall in their 1-year interview, although there was no effect for older children.…”
Section: Discussionmentioning
confidence: 99%